KORELASI ANTARA MOTIVASI BELAJAR DAN AKTIVITAS BELAJAR DENGAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS V SEKOLAH DASAR NEGERI 35 PONTIANAK SELATAN - Septiana Hutapea; Hery Kresnadi; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to analyze the correlation between learning motivation, learning activities and learning outcomes in thematic learning of fifth grade students. The method used is a descriptive method in the form of a correlation study research. The population in this study were all fifth grade students at SDN 35 South Pontianak. Sampling was done by using purposive sampling technique with a total of 35 students in class VA SDN 35 South Pontianak. The results showed that learning motivation was 86.86%, learning activities were 74.98% and learning outcomes were obtained an average of 74.98%. Statistical calculations using the product moment correlation formula, namely learning motivation with learning outcomes obtained rcount 0.160, learning activities with learning outcomes obtained rcount 0.461, and learning motivation with learning activities obtained rcount 0.458, for learning motivation and learning activities with learning outcomes using the double correlation formula obtained Ryx1x2 of 0.465 is in the category of moderate relationship with fcount of 4.414 and ftable = 5% of 4.15 which means Fcount (4.141) > Ftable (4.15). It can be concluded that there is a relationship between learning motivation and learning activities with learning outcomes in the thematic learning of class V Elementary School 35 South Pontianak.Keywords : Correlation, Activities, Motivation, Outcomes, and Learning